A case study of a transported bromine explosion event in the Canadian high arctic - Zhao, X; Strong, K.; Adams, C.; Schofield, R.; Yang, X.; Richter, A.; Frieß, Udo; Blechschmidt, A.-M.; Koo, J.-H. (Journal of geophysical research. Atmospheres, 2016)
Ozone depletion events in the polar troposphere have been linked to extremely high concentrations of bromine, known as bromine explosion events (BEE). However, the optimum meteorological conditions for the occurrence of these events remain uncertain. On 4-5 April 2011, a combination of both blowing snow and a stable shallow boundary layer was observed during a BEE at Eureka, Canada (86.4°W, 80.1°N). Measurements made by a Multi-Axis Differential Optical Absorption Spectroscopy spectrometer were used to retrieve BrO profiles and partial columns. During this event, the near-surface BrO volume mixing ratio increased to 20 parts per trillion by volume, while ozone was depleted to 1 ppbv from the surface to 700 m. Back trajectories and Global Ozone Monitoring Experiment-2 satellite tropospheric BrO columns confirmed that this event originated from a bromine explosion over the Beaufort Sea. From 30 to 31 March, meteorological data showed high wind speeds (24 m/s) and elevated boundary layer heights ( 800 m) over the Beaufort Sea. Long-distance transportation ( 1800 km over 5 days) to Eureka indicated strong recycling of BrO within the bromine plume. This event was generally captured by a global chemistry-climate model when a sea-salt bromine source from blowing snow was included. A model sensitivity study indicated that the surface BrO at Eureka was controlled by both local photochemistry and boundary layer dynamics. Comparison of the model results with both ground-based and satellite measurements confirmed that the BEE observed at Eureka was triggered by transport of enhanced BrO from the Beaufort Sea followed by local production/recycling under stable atmospheric shallow boundary layer conditions.
First published: 07 December 2015
Gesehen am 08.10.2021